Dynamics of Bothryocephalus sp. Infection in Fry and Fingerling of Carp in Warm-Water Cage Culture Fishery at Natural Water Temperature - D. P. Skachkov; Y. A. Pukhovsky; V. T. Orlov (Российский паразитологический журнал, 2019)
The purpose of the research is to study the seasonal dynamics of infection of fry and fingerling of carp with Bothryocephalus sp. in warm-water cage culture fishery with the complete absence of discharge of warm water into the cooler pond.Materials and methods. To determine the dynamics of infection of fry and fingerling of carp, we selected 3 cages with carp fry 1.5–2 g from the Cherepets Fish Farm. After transferring carp fry from the trays of the incubation workshop to cages, from July 25 to October 4, 2018, helminthological dissection of 10 fry and fingerling of carp from each experimental cage was performed to determine the extent and intensity of infection by Bothryocephalus sp. The content of soluble oxygen in the water was determined daily and the temperature of the water was measured in the area where the cage lines were located. After therapeutic deworming of the fingerling of carp with a fodder and medicated mixture with Microsal at a water temperature of 15°C, the fish from all experimental cages were dissected, after which the extensity and intensity of the treatment were determined.Results and discussion. The water temperature in the zone of location of cages with fingerling was 20–23°C. The mass of fingerling reached 1.5–2 g by July 25. On July 25, they caught and made helminthologic dissection of 10 carp fingerlings from cages No. 56, 67 and 78. No fish cestode was found. On August 23, when catching and helminthological dissection of carp fingerling from cages No. 56 and 78, the infection rate of fish by Bothriocephalus sp. was 20%, and in cage No. 67 – 10%. The infection rate was 1–2 cestodes per fish. Upon catch and helminthological dissection of carp fingerling No. 56, 67 and 78 on September 25, the infection rate of fish by Bothryocephalus sp. was 60%, 50%, and 50% respectively with an infection rate of 1 to 4 cestodes per fish. After therapeutic deworming of carp fingerlings with fodder and medicated mixtures with Microsal on October 4, 2018, the infection rate in fish in the control cage (No. 56) was 60% with an infection rate of 1 to 4 cestodes per fish. No cestode was found in carp fingerlings from cage No. 67. EE and IE – 100%. In cage number 78, one cestode was found in one fish. EE – 83.3% with IE – 90.9%.